Chronic Disseminated Candidiasis Complicated by Immune Reconstitution Inflammatory Syndrome in Child with Acute Lymphoblastic Leukemia - Olga Zając-Spychała; Bogna Ukielska; Katarzyna Jończyk-Potoczna; Benigna Konatkowska; Jacek Wachowiak (Case Reports in Hematology)
Hepatosplenic candidiasis also known as chronic disseminated candidiasis is a rare manifestation of invasive fungal infection typically observed in patients with acute leukemia in prolonged, deep neutropenia. Immune reconstitution inflammatory syndrome (IRIS) is an inflammatory disorder triggered by rapid resolution of neutropenia. Diagnosis and treatment of IRIS are still challenging due to a variety of clinical symptoms, lack of certain diagnostic criteria, and no standards of treatment. The diagnosis of IRIS is even more difficult in patients with hematological malignancies complicated by “probable” invasive fungal infection, when fungal pathogen is still uncertain. We report a case of probable hepatic candidiasis in 4-year-old boy with acute lymphoblastic leukemia. Despite proper antifungal therapy, there was no clinical and radiological improvement, so diagnosis of Candida-related IRIS was made and corticosteroid therapy was added to antifungal treatment achieving prompt resolution of infection symptoms.